Integrative Approaches for Mechanical Mold Design in Injection Molding. Issue 6 (1st June 2013) - Hopmann, Christian; Erler, Ivo
Abstract : The injection mold faces a number of different loads during the injection molding process for plastic parts. The effect on the mechanical behavior of the mold, inserts, and adjacent processes can be complex and may cause bad final parts. By using an integrative simulation approach it is possible to take the process influence into account when calculating the solid body behavior of the mold in a structural simulation. A newly developed approach at IKV uses the advantages of the integrative approach and extends it by an automatic back coupling of deformation results during the filling simulation. This way the interaction of the melt flow and the deformation of inserts or mold components can be considered during the filling phase.